Insight into the stabilization mechanism and long-term effect on As, Cd, and Pb in soil using zeolite-supported nanoscale zero-valent iron. (25th June 2022) - He, Yinhai; Fang, Tingting; Wang, Juan; Liu, Xiaoyang; Yan, Zengguang; Lin, Hai; Li, Fasheng; Guo, Guanlin
Abstract: Nanoscale zero-valent iron-based materials exhibited excellently for simultaneous remediation of arsenic(As), cadmium(Cd), and lead(Pb) co-contaminated soil. However, the instinct mechanism for stabilizing the three heavy metal(loid)s remains unclear. This study used the simplified zeolite-supported nanoscale zero-valent iron (Z-NZVI) to reduce As, Cd, and Pb availability, the remediation process characteristics, and the long-term stabilization mechanism were systematically investigated. Compared with the control, 1.0% of Z-NZVI performed highly efficiently for simultaneous stabilization of As, Cd, and Pb, and their availability decreased by 91.6%, 85%, and 96.6%, respectively, mainly due to the transformation of labile forms into residual. Furthermore, the availability of As, Cd and Pb was significantly positive with soil pH and negative with soil Eh (P < 0.01), respectively, indicating the soil pH and Eh should be priority regulated during the stabilization process. HRTEM-EDS, FTIR, XRD, and XPS characterizations of the magnetically separated Z-NZVI from incubated soil confirmed that the formation of coprecipitation together and the surface complexes transformed labile As into stable forms, complexation dominated Cd remediation, whereas Pb stabilization was mainly attributed to reduction and the formation of B-type ternary surface complexes by various Fe-containing substances. The simulated acid rain leaching results showed that Z-NZVI effectively restrained As, Cd, and Pb leaching by 97.7%, 92.8%, and 93.4%, respectively, revealing the long-term stabilization effect on the three heavy metal(loid)s. This research demonstrated that Z-NZVI is a promising amendment for realizing the simultaneous stabilization of As, Cd, and Pb in co-contaminated soil. Graphical abstract: Image 1